Nonlinear regression models for estimating linseed growth, with proposals for data collection - Mariane Peripolli; Alessandro Dal'Col Lúcio; Darlei Michalski Lambrecht; Jaqueline Sgarbossa; Lana Bruna de Oliveira Engers; Sidinei José Lopes; Leosane Cristina Bosco; Dislaine Becker (Acta Scientiarum. Agronomy, 2024)
Nonlinear regression models represent an alternative way to describe plant growth. In this study, we aimed to model the growth of linseed using four methods for data collection (longitudinal, mean, random, and cross-sectional) and fitting the logistic and Von Bertalanffy nonlinear regression models. The data came from experiments conducted between 2014 and 2020 in the municipality of Curitibanos, Santa Catarina, Brazil. The study had a randomized block design, with experimental units consisting of six lines, 5.0 m long and 3.0 m wide, containing the varieties and cultivars of linseed with four replicates. We performed weekly assessments of the number of secondary stems and plant height and measured total dry mass fortnightly. After tabulation, the data were analyzed using the four methods, and the logistic and Von Bertalanffy models were fitted. The logistic model for the plant height variable exhibited the best performance using the longitudinal, mean, and cross-sectional methods. It was an alternative approach that reduced the time and labor required to conduct the experiment.